2020
DOI: 10.1021/acs.joc.0c01841
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Cycloisomerization of 1,6-Cyclohexenylalkyne: An Efficient Entry to Bicyclo[3.2.1]oct-2-ene and Bicyclo[3.3.1]nonadiene

Abstract: An efficient and mild synthetic route for the preparation of functionalized bicyclo[3.2.1]­oct-2-ene and bicyclo[3.3.1]­nonadiene via gold-mediated cycloisomerization of 1,6-enynes has been developed. This atom-economical catalytic process was optimized and relied on the efficiency of IPrAuNTf2 allowing the formation of functionalized bicyclic adducts in 55–91% isolated yields (18 products). The reliable access to bicyclic derivatives was demonstrated on a 3 g scale with a low catalyst loading. The process occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…At the outset of our study, we prepared several functionalized 1,6-enynes, starting from ethyl 4-cyclohexanone-carboxylate according to a straightforward three-step route implying a triflate formation, a Suzuki-Miyaura coupling and a propargylation (Scheme 2). We prepared non-substituted alkynes 1a-d as well as substituted ones such as Mesubstituted 1e, and Ar-substituted 1f-1p, the latter being obtained via classical Sonogashira cross-coupling reactions on 1a [22]. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the outset of our study, we prepared several functionalized 1,6-enynes, starting from ethyl 4-cyclohexanone-carboxylate according to a straightforward three-step route implying a triflate formation, a Suzuki-Miyaura coupling and a propargylation (Scheme 2). We prepared non-substituted alkynes 1a-d as well as substituted ones such as Mesubstituted 1e, and Ar-substituted 1f-1p, the latter being obtained via classical Sonogashira cross-coupling reactions on 1a [22]. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…At the outset of our study, we prepared several functionalized 1,6-enynes, starting from ethyl 4-cyclohexanone-carboxylate according to a straightforward three-step route implying a triflate formation, a Suzuki-Miyaura coupling and a propargylation (Scheme 2). We prepared non-substituted alkynes 1a-d as well as substituted ones such as Me substituted 1e, and Ar-substituted 1f-1p, the latter being obtained via classical So nogashira cross-coupling reactions on 1a [22]. Based on our gold-catalyzed experience, we have recently studied the cycloisomerization reactions of the known ethyl 4-oxocyclohexane carboxylate 1a and showed that the use of gold catalysts allowed the formation of bicyclo[3.2.1]oct-2-ene 2a as well as the isomerized 3a in various ratio depending on the gold catalyst (Table 1, entries 1-3) [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These novel building blocks contribute to the “escape from flat‐land” concept [17] and prompt us to further explore this type of skeleton by studying the unprecedented gold‐catalyzed cyclization of alkynyl cyclohexenyl derivatives [18] . The gold‐catalyzed cycloisomerization of 1,6‐enynes derived from ethyl 4‐oxocyclohexane carboxylate was thus recently optimized leading to the preparation of functionalized bicyclo[3.2.1]oct‐2‐ene and bicyclo[3.3.1]nonadiene under mild conditions (Scheme 5, Table 2).…”
Section: Cycloisomerization and Domino Reactions Of 15‐ And 16‐enynesmentioning
confidence: 99%